Method for producing electrode for ignition device

By adopting two-dimensional bonding technology below the melting temperature in the ignition device, the problem of easy corrosion, shrinkage and cracks in the weld is solved, achieving a longer service life and higher thermal conduction performance.

CN119563265APending Publication Date: 2025-03-04SWACRIT SYST GMBH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380045924.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-25
Filing Date
2023-05-25
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, the weld combination between the precious metal electrode and the carrier has problems with corrosion tendencies, shrinkage holes and cracks, resulting in a short service life, frequent maintenance and high cost of the ignition device.

Method used

By forming a two-dimensional bond between the carrier material and the electrode material with a bonding temperature below its melting temperature, metal bonds are formed using the diffusion process to reduce thermal stress and corrosion risks during welding.

Benefits of technology

The high-strength and crack-free combination between the electrode material and the carrier material is achieved, which extends the service life of the ignition device, reduces maintenance costs, and improves the heat conduction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563265A_ABST
    Figure CN119563265A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing an electrode for an ignition device, in particular a spark plug, in which a metal electrode material (2) is placed against a metal carrier material (1) at a joining surface (8), in which the carrier material (1) and the electrode material (2) are pressed against each other at the joining surface (8) at a specific surface pressure and placed in a chamber in which a reduced pressure, in particular a vacuum, is generated, the bonding surface (8), in particular the carrier material (1) and the electrode material (2), is uniformly heated to a bonding temperature (TF), and wherein the bonding temperature (TF) is maintained for a bonding time (tF), and wherein a reduced pressure and / or a specific atmosphere are / is applied in the chamber, and wherein the bonding surface (8), in particular the carrier material (1) and the electrode material (2), is uniformly heated to a bonding temperature (TF). The carrier material (1) and the electrode material (2) are bonded to each other in order to form a bond between the carrier material (1) and the electrode material (2) at the bonding surface (8), and the carrier material (1) and the electrode material (2) form a two-dimensional, in particular full-surface, uniform bond to each other starting from the bonding surface (8). According to the invention, the bonding temperature (TF) is lower than the melting temperature (TS) of the carrier material (1) and the electrode material (2).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a method for producing an electrode for an ignition device according to the preamble of claim 1, a method for producing a spark plug according to the preamble of claim 18, a spark plug according to the preamble of claim 19 and an ignition device according to the preamble of claim 21.

[0002] The prior art discloses various ignition devices, whereby a combustible medium or a combustible mixture is ignited by applying a spark from an electrode. The expanding gas upon ignition causes a change in pressure conditions, which is then usually converted into mechanical work. Such ignition devices can be used, for example, in motor vehicles, gas engines or other devices known in the prior art.

[0003] The prior art also discloses methods for producing such ignition devices. In the methods known from the prior art, for example in the case of spark plugs, an ignition gap is formed between two electrodes, for example between a central electrode comprising a noble metal electrode and a ground electrode. A potential difference is then applied to the noble metal electrode and a spark is generated across the ignition gap. The noble metal electrode usually consists of a platinum alloy or an iridium alloy or other alloys arranged on a nickel carrier. In the prior art, the bond between the nickel carrier and the noble metal electrode is produced by laser welding. Laser welding starting from the surface of the object results in a material-matched linear bond between the noble metal electrode and the carrier, wherein there is a low bond thickness in the center of the contact area.

[0004] EP 2738890 A1 (TANAKA PRECIOUS METAL IND) published on June 4, 2014, DE 112019000377 T5 (NGK SPARK PLUG CO) published on September 17, 2020, US 6750597 B1 (SAKURA, A.) published on June 15, 2004, EP 3139457 A1 (NGK SPARK PLUG CO) published on March 8, 2017, and DE 112016006310 T5 (NGK SPARK PLUG CO) published on October 11, 2018 each disclose a method and a spark plug in which a precious metal electrode is fixed to a carrier material by means of welding.

[0005] However, the methods known from the prior art have the disadvantage that the bond between the noble metal electrode and the carrier at the weld seam is prone to corrosion and therefore requires special protection. Such a method for producing spark plugs by welding is known, for example, from EP 3 694 684 A1, wherein the weld seam formed is subsequently post-treated to prevent corrosion.

[0006] Another disadvantage of the bonding methods known from the prior art is that shrinkage cavities often occur in the weld during the welding process, which reduce the strength of the bond. In addition, cracks often form in the heat-affected zone during the weld bond, which can also reduce the strength of the weld bond. It has therefore been found in practice that ignition devices according to the prior art generally have a short service life and are very significantly prone to high wear, severe corrosion and, in many cases, detachment of precious metal sheets. Therefore, in the prior art, the spark plugs must be checked or replaced at regular short intervals, which leads to a high level of maintenance and frequent downtimes, which seriously impairs economical operation.

[0007] It is also disadvantageous that when an inhomogeneous bond is produced between two materials by means of a weld, the two materials only melt at certain points, so that warping and / or internal stresses occur due to the inhomogeneous dissipation of the heat introduced along the weld or heat-affected zone. This causes inhomogeneous heat dissipation and point overheating of the joining site during operation, as well as mechanical stresses due to thermal expansion in the joining zone, which promote the peeling of the precious metal sheet.

[0008] It is therefore an object of the present invention to provide a method for producing an ignition device which enables a longer service life of the ignition device, in particular for an ignition device in the form of a spark plug.

[0009] This object is achieved by the characterizing features in the method according to the preamble of claim 1. According to the invention, it is provided that the joining temperature is below the melting temperature of the carrier material and of the electrode material.

[0010] If the joining temperature is below the melting temperature of the support material and the electrode material, a special bond between the electrode material and the support material is brought about by the diffusion of individual atoms or ions of these materials into the respective other material, for example individual atoms or ions of the support material into the electrode material or vice versa. In this way, the diffusion process leads to a particularly strong two-dimensional bond along or within the joining surface.

[0011] The features of the invention make it possible to produce a bond between carrier material and electrode material which has a high strength due to the two-dimensional bonding of the two materials. The two-dimensional bonding in the form of a metallic bond further reduces the risk of crack formation and corrosion in the joint area, thereby reducing in particular unplanned or overly frequent maintenance costs and avoiding costs in spark plug renewal or component replacement, or reducing the costs of the entire ignition device or spark plug. The uniform heating of the joint surface also avoids the introduction of thermal stresses into the joint surface, thereby avoiding stress cracks and internal stresses in the two-dimensional bond between electrode material and carrier material and warping of the component.

[0012] The uniform increase in temperature to the joining temperature and the elimination of a point-shaped or line-shaped weld pool in the joining surface as in the case of fusion welding also make it possible to better control the heat supply and thus make the components, in particular the electrode material, smaller or thinner. Since the electrode material consists or can consist of expensive noble metals, this leads to a significant reduction in material costs. The method according to the invention therefore also allows, unlike laser welding known to date in the prior art, electrode material thicknesses of less than 0.5 mm to be processed.

[0013] Furthermore, studies of ignition devices produced by the method according to the invention have shown that these have a significantly longer service life than the prior art.

[0014] For the purposes of the present invention, the joining time is defined as the time period during which the joining temperature is maintained and / or is greater than or equal to a threshold temperature, in particular 30% of the melting temperature of the carrier material and / or the electrode material, wherein other temperature distributions may also exist at the joining surface before and / or after the joining time. For example, there may be a prior or subsequent heating phase and / or cooling phase, and / or the joining temperature may also vary within a certain range. For the purposes of the present invention, the joining temperature is understood to mean not only a constant temperature, but also a temperature that may vary during the joining time. The joining temperature is understood to mean the temperature at which a bond can be generated between the electrode material and the carrier material. During the research process that is the basis of the present invention, it was surprisingly found that the joining temperature in most of the tested materials was higher than 30% of its melting temperature but lower than 50% of its melting temperature, in particular the melting temperature of materials with a higher melting temperature. In addition, it was found that higher temperatures can accelerate the bonding process and thus shorten the bonding time depending on the temperature.

[0015] Two-dimensional bonding is understood in the present invention to mean that the carrier material and the electrode material form a two-dimensional, especially full-surface, and uniform bond in the form of a metallic bond along the entire joint surface, i.e. across the entire area where the carrier material and the electrode material are in contact. The electrode produced by the production method of the present invention therefore has not only a linearly bonded section at the edge area of ​​the joint surface as in the case of a weld seam, but is also bonded to one another two-dimensionally or full-surface and uniformly at least in a large part of the joint surface, especially across the entire joint surface.

[0016] The full-surface bond between electrode material and carrier material also enables a higher heat conduction and thus a cooler electrode during use.

[0017] Possible spark erosion in the ignition device can occur in an undesirable manner in the edge region of the electrode, which in the case of linear bonds leads to a shortened service life due to its limitation to the edge region of the joint surface. In contrast, in the case of two-dimensional bonds, such as in the case of electrodes produced by the method according to the invention, spark erosion constitutes a negligible effect.

[0018] Particularly advantageous embodiments of the method according to the invention are defined in detail by the features of the dependent claims:

[0019] Preferably, in the method according to the invention, the heat which is released to the joining surfaces, in particular the carrier material and the electrode material, to raise them to the joining temperature is generated by induction, radiant heat or heat conduction.

[0020] It can be preferably provided that the joining temperature is maintained for a joining time in order to form a metallic bond based on metallic bonds without forming an intermetallic phase between the carrier material and the electrode material, wherein in particular, the diffusion of atoms and / or ions of the electrode material into the carrier material and / or the diffusion of atoms and / or ions of the carrier material into the electrode material is greater than or equal to 0.05 μm, in particular 1 μm to 100 μm, more preferably 20 μm to 40 μm. The so-called "diffusion bonding" achieved results in a particularly strong metallic bond between the carrier material and the electrode material, which does not cause any intermetallic phase between the two materials. Due to the absence of the formation of an intermetallic phase, weakening of the material or weakening of the bond between the two materials is also prevented to prevent the formation of cracks and shrinkage cavities and other strength-reducing effects.

[0021] “Diffusion” in this context is understood to mean the depth to which atoms and / or ions of the carrier material and / or electrode material penetrate into the respective other material. This can also alternatively be referred to as the diffusion depth.

[0022] It has proven to be advantageous to apply the carrier material and the electrode material to a pressure of 10 mN / mm 2 Up to 2500mN / mm 2 , especially 100mN / mm 2 Up to 600mN / mm 2 The minimum surface pressure presses against each other.

[0023] In order to be able to effectively prevent the adverse effects of a destructive atmosphere and to bring about a favorable bond formation at the joining surfaces, it can be provided that the method is carried out under vacuum, under reduced pressure and / or under a low-oxygen, especially oxygen-free atmosphere and / or under an inert and / or reducing atmosphere, wherein the vacuum, reduced pressure and / or low-oxygen, especially oxygen-free atmosphere and / or the inert and / or reducing atmosphere are changed during the course of the method.

[0024] In an advantageous embodiment, provision can be made for the joining temperature to be 30% to 100%, in particular 50% to 98%, more preferably 75% to 95%, of the melting temperature of the carrier material and / or the electrode material.

[0025] By having a joining time of 1 minute to 24 hours, in particular 1 hour to 4 hours, more preferably 1 hour to 2 hours, after exceeding a threshold temperature of 30% of the melting temperature of the carrier material and / or the electrode material, the two materials can be effectively joined in a particularly efficient manner. Thus, it can be provided that the joining time is measured only after exceeding the threshold temperature, or that the joining temperature is kept constant and / or above the threshold temperature during the joining time.

[0026] In an optional embodiment of the method, it can be provided that the joint surface has a 2 Up to 50mm 2 , especially 2mm 2 Up to 30mm 2 , more preferably 2mm 2 Up to 15mm 2 size.

[0027] The method of the invention allows the electrode material to have a thickness of 0.05 mm to 2 mm, in particular 0.05 mm to 0.5 mm, more preferably 0.05 mm to 0.25 mm. In this way, by a particularly thin formation of the electrode material, positive properties of the electrode material can be achieved at low material costs.

[0028] An effective combination between the two materials is provided in particular as follows: the support material consists of a material selected from the group of elements 4 to 11 or the group of titanium, vanadium, chromium, manganese, iron, cobalt, nickel or copper, in particular of the material nickel, iron, chromium, molybdenum, tungsten or alloys thereof, more preferably VDM Nickel 201 or EN 2.4068, including steel, Inconel and refractory metals, and the electrode material consists of a material selected from the group of elements 4 to 11 or the group of titanium, vanadium, chromium, manganese, iron, cobalt, nickel or copper, in particular of platinum, iridium, rhodium, ruthenium, rhenium or alloys thereof, more preferably of PtRh 90 / 10 and IrRh 90 / 10 from Heraeus. "Element group" is understood in the present invention to mean the respective group of the periodic table, which is also referred to as the main group and transition group, in which all elements have the same number of valence electrons in each case. The definition of the term "element group" or "group of the periodic table" or "group in the periodic table" according to the present invention can be found in the textbook [Handbuch Maschinenbau, Alfred 2011, ISBN 978-3-8348-1025-0] or Wikipedia.

[0029] An optional embodiment of the method of the invention is provided that, before or after positioning the electrode material on the carrier material, a solder is applied or installed or introduced on the joint surface and / or next to the joint surface, wherein the joining temperature is higher than the melting temperature of the solder and in each case lower than the melting temperature of the carrier material and the electrode material, wherein the joining time after exceeding the melting temperature of the solder is in particular 10 seconds to 2 hours, preferably 1 minute to 60 minutes. The introduction of the solder on the joint surface and / or next to the joint surface results in the two materials forming an advantageous two-dimensional bond via the solder, which is reliably maintained even under the effect of thermal stresses or internal stresses and ignition forces or when an ignition current flows. The joining time in the welding operation is understood to mean the time period during which the temperature of the joint surface, the electrode material and / or the carrier material and / or the solder remains above the melting temperature of the solder.

[0030] It is advantageously provided here that the solder base material of the solder is selected from element groups 9 to 11 or the cobalt, nickel or copper group or alloys thereof, wherein the solder base material of the solder contains in particular alloying additives from element groups 4 to 15, wherein the solder consists in particular of silver, gold or nickel as solder base material and contains optional additives such as chromium, silicon, iron, boron, molybdenum, phosphorus, palladium and / or copper or combinations thereof, wherein the solder is preferably Ag 99.99 or NiCrSiBFe or NiCrSi.

[0031] In an optional embodiment of the method, it is provided that the carrier material has a recess, wherein the electrode material is at least partially sunken into the recess when placed against the carrier material. The formation of a plurality of recesses or a recess in the carrier material makes it easier to position the electrode material and in this way it is optionally possible to achieve an extension of the joining surface beyond the side edges of the electrode material or the carrier material to the side of the recess.

[0032] In a further optional embodiment of the method according to the invention, it is provided that an intermediate material is arranged between the carrier material and the electrode material, on the carrier material or on the electrode material, wherein a joining surface is formed between the carrier material and the intermediate material and between the electrode material and the intermediate material in each case, wherein the joining temperature is below the melting temperature of the carrier material and the electrode material and the intermediate material, wherein the carrier material and the intermediate material form a two-dimensional bond to one another and the electrode material and the intermediate material form a two-dimensional bond to one another in each case. In this way, it is also possible to bond materials that are originally weakly bonded to one another to one another via the intermediate material, so that these materials form a two-dimensional bond to one another via the intermediate material in the form of a metallic bond.

[0033] Optionally, it can be provided that the intermediate material takes the form of a diffusion accelerating material, in particular silver or copper, wherein the diffusion of atoms and / or ions of the electrode material via the intermediate material into the carrier material and / or the diffusion of atoms and / or ions of the carrier material into the electrode material via the intermediate material is accelerated by the intermediate material. With the intermediate material in the form of a diffusion accelerator or acting as a diffusion accelerator, the diffusion of atoms and / or ions of the electrode material via the intermediate material into the carrier material and / or the diffusion of atoms and / or ions of the carrier material into the electrode material via the intermediate material can be accelerated.

[0034] Optionally, it can be provided that the carrier material and / or the electrode material and / or the intermediate material have an average roughness Ra of 0.01 μm to 6.3 μm, in particular 0.02 μm to 0.5 μm, at the joint surface. The favorable surface properties of these materials lead to particularly favorable two-dimensional bonding between the materials and in particular improve diffusion or diffusion bonding.

[0035] In order to be able to produce a plurality of electrodes simultaneously, it can be provided that a plurality of carrier materials and electrode materials are each arranged in pairs in a stack, wherein the carrier materials and electrode materials to be combined in pairs are in each case separated from one another by a separator material and / or a separator layer relative to the other pairs. The separator material or the separator layer does not enter into any bonding with the electrode material or the carrier material during the process, so that the two materials can each be easily lifted, peeled off or separated from the separator material or from the separator layer.

[0036] A further aspect of the invention provides for providing a method for producing a spark plug which has a longer service life and a stronger bond between electrode material and carrier material than in the prior art.

[0037] This object is achieved by the characterizing features of claim 18. According to the invention, it is provided that the bond between carrier and electrode sheet is produced by the method according to the invention.

[0038] The method according to the invention for producing a spark plug can be carried out simply and inexpensively, in such a way that a strong two-dimensional bond can be produced between the electrode sheet and the carrier body which prevents corrosion and crack formation.

[0039] A further aspect of the invention provides for a spark plug, in particular for an internal combustion engine or a gas engine, which has an electrode according to the invention or an electrode consisting of an electrode material which has a particularly good bond to a carrier material.

[0040] This object is achieved by the characterizing features in a spark plug according to the preamble of claim 19. According to the invention, it is provided that the bond between a carrier and an electrode sheet is produced by the method according to the invention, wherein the carrier is in the form of a carrier material and the electrode sheet is in the form of an electrode material.

[0041] The spark plug according to the invention has a particularly strong bond between the carrier and the electrode, which is protected from adverse effects occurring during the ignition process, so that it can also be used with a long service life and high reliability when used as a high-performance spark plug in which high potential differences occur and high thermal durability is simultaneously required. The spark plug according to the invention is able to withstand high potential differences and at the same time high thermal or alternating stresses.

[0042] An advantageous embodiment of the spark plug according to the invention can be provided in that the carrier is formed from a titanium, nickel or iron material, in particular from a nickel or chromium-nickel alloy or steel or Inconel or a refractory metal, preferably from nickel in pure form, a nickel-based alloy, FeCrNi or FeCrNiMo stainless steel, and wherein the electrode sheet is formed from a noble metal, in particular platinum, iridium, rhodium, ruthenium, rhenium or an alloy thereof, in particular a platinum / rhodium, platinum / rhenium, platinum / iridium, iridium / rhenium or iridium / rhodium alloy, wherein the electrode sheet more preferably comprises an alloy of PtRh 90 / 10 or an alloy of IrRh 90 / 10 and the carrier comprises an alloy of VDMNickel 201 or EN 2.4068.

[0043] Another aspect of the invention provides for providing an ignition device with a favorable bond between the carrier and the electrode sheet. This object is achieved by the characterizing features of claim 21; according to the invention, it is provided that the carrier and the electrode sheet form a two-dimensional, in particular full-surface, uniform bond with each other, wherein in particular the carrier is in the form of a carrier material and the electrode sheet is in the form of an electrode material, wherein a diffusion zone is formed in the two-dimensional bonding region between the carrier and the electrode sheet, wherein there is a concentration of 100% to 0% of the material of the carrier in the direction of the electrode sheet from the carrier and a concentration of 0% to 100% of the material of the electrode sheet from the carrier (in the direction of the electrode sheet), wherein in particular the diffusion depth is greater than or equal to 0.05 μm, in particular 1 μm to 100 μm, more preferably 20 μm to 40 μm.

[0044] Preferably, it is provided that the carrier is formed from a titanium, nickel or iron material, in particular from a nickel or chromium-nickel alloy or steel or Inconel or a refractory metal, preferably from nickel, a nickel-based alloy, FeCrNi or FeCrNiMo stainless steel in pure form, and wherein the electrode sheet is formed from a noble metal, in particular platinum, iridium, rhodium, ruthenium, rhenium or an alloy thereof, in particular a platinum / rhodium, platinum / rhenium, platinum / iridium, iridium / rhenium or iridium / rhodium alloy, wherein the electrode sheet more preferably comprises an alloy of PtRh 90 / 10 and / or the electrode sheet comprises an alloy of IrRh 90 / 10 and the carrier comprises an alloy of VDM Nickel 201 or EN 2.4068.

[0045] Further advantages and configurations of the invention are apparent from the description and drawings.

[0046] The invention is schematically illustrated below by means of particularly advantageous embodiments which are not to be understood as limiting and are described by way of example with reference to the accompanying drawings:

[0047] Figure 1 The electrode produced by the method of the present invention is shown schematically. Figure 1a to Figure 1d The different temperature-time diagrams of the production method of the electrode of the present invention are shown in simplified diagrams, Figure 2 Schematic diagram showing electrodes produced with solder, Figure 3 showing electrodes with intermediate materials, Figure 4 A schematic diagram showing an electrode having a recess, Figure 5 The image of the electrode of the present invention under an electron microscope (FEI Quanta 3D 200 scanning electron microscope) is shown. Figure 6 Display according to Figure 5 Another image under an electron microscope with higher magnification, Figure 7 Display according to Figure 5 and 6 The distribution of various elements of the electrode in the joint surface area, Figure 8 Another image showing one embodiment of an electrode of the present invention under an electron microscope, Fig. 9 Display according to Figure 8 The electrode is imaged at a higher magnification. Fig.10 Display according to Figure 8 and 9 The distribution of elements in the electrode joint area, Fig.11 An image of the electrode of the present invention produced by welding under an electron microscope (JEOL-JSM-IT200-LA with EDX unit) is shown. Fig.11a show Fig.11 The temperature evolution of the electrode production method depicted in Fig.11b show Fig.11 The pressure distribution and vacuum conditions of the electrode production method depicted in the figure are shown in Fig. Fig.12 Display according to Figures 5 to 10 A temperature profile of an embodiment of a method for producing an electrode, Fig.13 Display according to Fig.12 A diagram of the pressure distribution and vacuum conditions of an embodiment of the production method of the present invention, Fig.14 An image showing a microscopic section of an electrode of the present invention, Fig.15 A microscopic cross-section of an electrode from a prior art spark plug is shown. Fig.16 The spark plug of the present invention is shown schematically. Fig.17 An alternative embodiment of the spark plug of the present invention is shown in isometric view, and Fig.18 One embodiment of the production method of the present invention for producing a plurality of electrodes is shown.

[0048] Figure 1 A first electrode according to the invention for an ignition device is shown in a schematic diagram. The electrode comprises a metallic carrier material 1 which is bonded to an electrode material 2 of the same metal at a joining surface 8 . Figure 1 The electrode shown in is produced by the method of the present invention. To produce the electrode, a metal electrode material 2 is placed close to a metal carrier material 1 at a joint surface 8 so that it adjoins the carrier material 1 in a two-dimensional manner. The carrier material 1 and the electrode material 2 are pressed against each other at the joint surface 8 with a specific surface pressure and placed in a chamber in which a reduced pressure, a vacuum and / or a specific atmosphere can be generated. After positioning the carrier material 1 and the electrode material 2, a reduced pressure or a specific atmosphere is applied in the chamber. After applying the specific atmosphere or reduced pressure, the joint surface 8 is heated to a joint temperature T F , and keep it engaged for a specific time t F The electrode material 2 is pressed against the carrier material 1 and heated to the bonding temperature T F A two-dimensional bonding of the carrier material 1 and the electrode material 2 is achieved. The bonding temperature T in the method of the present invention is F Below the melting temperature T of the carrier material 1 S and lower than the melting temperature T of electrode material 2 S .

[0049] Figure 1 The electrode shown in FIG. 1 is produced by a so-called diffusion bonding operation, wherein the bonding temperature T F Always below the melting temperature T of the carrier material 1 S and lower than the melting temperature T of electrode material 2 S . Set the junction temperature T F Keep engagement time t F , so as to form a metallic bond in the form of a metallic bond without forming an intermetallic phase between the support material 1 and the electrode material 2. The bonding temperature T F Keep engagement time t F The effect is that atoms and / or ions of the electrode material 2 penetrate into the carrier material 1 and vice versa. Surprisingly, this so-called "diffusion effect" was found in the experiments that form the basis of the present invention. It was found that, depending on the material pair, atoms or ions of the electrode material 2 diffuse into the carrier material 1 and / or vice versa and reach a diffusion depth d of at least 0.05 μm and more. F .

[0050] like Figure 1a As shown in the diagram of FIG. 1 , after the electrode material 2 has been placed against the carrier material 1 and a reduced pressure or atmosphere has been applied, the joint surface 8 or the entire carrier material 1 and the entire electrode material 2 are heated. A After that, the junction temperature TF , then keep engaged for time t F . Engagement time t F Maintain from 1 second to 24 hours, where the engagement time t F Especially 1 hour to 4 hours, more preferably 1 hour to 2 hours. F At the end, the heating process is then ended and the joint surface 8 or the electrode material 2 and the carrier material 1 are then cooled for a cooling time t K According to the present invention, the joining temperature T F is the melting temperature T of the carrier material 1 and / or the electrode material 2 S 30% to 100%, in particular the melting temperature T of the support material 1 and / or the electrode material 2 S 50% to 98%, more preferably 75% to 95%. For example, depending on the material pair, the joining temperature T F Therefore, it can be 77% of the melting temperature of the support material 1 and the melting temperature T of the electrode material 2. S 45% of.

[0051] Figure 1b Another diagram depicts a possible heating curve. Temperature T starts from a starting temperature, for example room temperature, at a heating time t A Internal heating to the threshold temperature T 阈值 When the threshold temperature T is reached 阈值 When the engagement time t F The temperature is then increased further, for example to the melting point T of one of the two materials. S or higher, and then lowered again. The temperature T of the material is then kept constant for a period of time, and then cooled again for a cooling time t after the bond has been formed. K .

[0052] like Figure 1c and 1d As shown in F Optionally, the temperature can be ramped only above the threshold temperature T 阈值 or first remain constant for a period of time and then increase and / or decrease further.

[0053] Junction temperature T F In each case it is above the threshold temperature T 阈值 This is the temperature at which the electrode material 2 and the carrier material 1 begin to form a bond. F You can Figure 1a as shown in the constant, or can be as Figures 1b to 1d The engagement time t F Internally variable.

[0054] In order to form a two-dimensional bond between the carrier material 1 and the electrode material 2, the two materials are pressed against each other at the joint surface 8 with a specific surface pressure during the production method of the electrode. According to the invention, it has been found that 10 mN / mm 2 Up to 2500mN / mm 2 , especially 100mN / mm 2 Up to 600mN / mm 2 The minimum surface pressure has a favorable effect on the bonding properties of the carrier material 1 and the electrode material 2.

[0055] In particular, depending on the materials used in the electrode material 2 and the carrier material 1, the method can be carried out under vacuum, reduced pressure and / or a low-oxygen, especially oxygen-free, atmosphere. The applied atmosphere can also optionally be an inert or reducing atmosphere. In the method for producing an electrode according to the invention, the joint surface 8 preferably has a thickness of 1 mm. 2 Up to 50mm 2 , especially 2mm 2 Up to 30mm 2 , more preferably 2mm 2 Up to 15mm 2 size.

[0056] Figure 2 Another embodiment of the electrode according to the invention produced by the second embodiment of the production method according to the invention is shown. For the bonding of the carrier material 1 and the electrode material 2, a solder 13 is additionally applied to the joint surface 8 or arranged next to the joint surface, and then the bonding temperature T F Increase to a temperature higher than the melting point of the solder S and lower than the melting temperature T of the support material 1 and the electrode material 2 S The application and joining temperature T of the solder 13 F Increase to a temperature higher than the melting temperature T of the solder 13 S The effect is that, in particular under reduced pressure or vacuum, the solder 13 melts and is sucked into the joint surface 8 or between the electrode material 2 and the carrier material 1 by capillary effect, thus forming a two-dimensional bond between the electrode material 2 and the carrier material 1. It has surprisingly been found that during the formation of the bond by means of the solder 13, some of the atoms and / or ions of the electrode material 2 and / or the carrier material 1 can optionally also penetrate via the solder 13 or across the joint surface 8 into the respective other material and improve the bond.

[0057] The solder 13 or solder base material is preferably selected from materials from element groups 9 to 11 or the cobalt, nickel or copper groups or alloys thereof. The solder base material contains, in particular, alloying additives from element groups 4 to 15, wherein silver, gold or nickel are particularly preferred as solder base materials, and additives containing chromium, silicon, boron, iron, molybdenum, phosphorus, palladium and / or copper and / or combinations thereof.

[0058] Figure 3 A further electrode produced by an optional embodiment of the method according to the invention is schematically depicted. An intermediate material 12 is arranged between the electrode material 2 and the carrier material 1, which is heated to the bonding temperature T F The intermediate material 12 can be inserted at the junction 8 between the carrier material 1 and the electrode material 2 to form a junction 8 between the carrier material 1 and the intermediate material 12 and between the electrode material 2 and the intermediate material 12 in each case. After applying a specific atmosphere and / or a vacuum or reduced pressure, the temperature in the junction 8 or the temperature of the intermediate material 12, the temperature of the carrier material 1 and the temperature of the electrode material 2 is then increased to the junction temperature T F , where the junction temperature T F At this time, it is lower than the melting temperature T of the carrier material 1. S and lower than the melting temperature T of electrode material 2 S and lower than the melting temperature T of the intermediate material 12 S At the junction temperature T F Keep engagement time t F Afterwards, a two-dimensional bond is then formed in each case between the support material 1 and the intermediate material 12, and a two-dimensional bond is formed between the electrode material 2 and the intermediate material 12. Optionally, it is also possible that atoms or ions of the electrode material 2 diffuse into the support material 1 via the intermediate material 12 and / or that atoms or ions of the support material 1 diffuse into the electrode material 2 via the intermediate material 12.

[0059] The intermediate material 12 may optionally also take the form of a diffusion accelerator, wherein in this case the intermediate material in particular consists of a thin layer of copper or silver or comprises a thin layer of copper or silver. The intermediate material 12 in the form of a diffusion accelerator can accelerate the diffusion of atoms and / or ions of the electrode material 2 via the intermediate material 12 into the carrier material 1 and / or the diffusion of atoms and / or ions of the carrier material 1 into the electrode material 2 via the intermediate material 12. Thus, it has been surprisingly found that a silver thin layer with a thickness of 100 nm can be formed at a bonding temperature T of about 95% of the melting temperature of the silver material. F In this case, the diffusion is accelerated by about 40 times.

[0060] Figure 4A recess 11 formed in the carrier material 1 is shown, wherein the electrode material 2 is at least partially sunken and arranged in the recess when placed against the carrier material 1. This may optionally extend the joint surface 8 beyond the edge of the electrode material 2 and optionally facilitate the positioning of the electrode material 2 on the carrier material 1, and help to increase the bonding strength in the joint surface 8. Alternatively, it is also possible that the recess 11 is formed spontaneously during the production method or the electrode material 2 is introduced into the carrier material 1 spontaneously. That is, it is presumed that, especially in the case of a diffusion process, the penetration of atoms or ions of the electrode material 2 into the carrier material 1 causes the entire electrode material 2 to partially penetrate into the carrier material 1, and in this way the recess 11 can be formed.

[0061] In such Fig.18 In another embodiment of the method of the present invention shown in , it is provided that a plurality of carrier materials 1 and electrode materials 2 are co-positioned in a chamber to apply a specific atmosphere and / or vacuum or reduced pressure. In this case, the carrier material 1 is placed close to the electrode material 2 in each case, and the resulting paired arrangement is, for example, each stacked into a so-called "stack", or positioned at a certain distance from each other. The carrier material 1 and the electrode material 2 to be combined in pairs can each be separated from each other by a separator 19 or a separator layer. The separator 19 is a material that is neither combined with the electrode material 2 nor with the carrier material 1, or prevents the carrier material 1 and the electrode material 2 from combining with each other in pairs.

[0062] Figure 5 An image of the joint surface 8 of the electrode produced by the method of the present invention at a magnification of 70:1 recorded by an electron microscope of a FEIQuanta 3D 200 scanning electron microscope is shown. The electrode has a carrier material 1, on which an electrode material 2 has been placed close to the joint surface 8 and has been formed into a two-dimensional bond by means of the method of the present invention. The electrode material 2 has a size of 1.7 mm x 2.2 mm and a thickness of 0.5 mm. The electrode material 2 consists of a platinum-rhodium alloy PtRh 90 / 10 from Heraeus. The carrier material 1 in this embodiment consists of a nickel alloy VDM Nickel201, also known as EN 2.4068.

[0063] Figure 6 Displays the image at an increased resolution (1024 x 943 @ 96 dpi, bit depth 24, magnification 250:1) Figure 5 Magnified image of the junction surface 8 of the electrode. It is obvious at the junction surface 8 that atoms or ions of the electrode material 2 have diffused into the support material 1 due to the method of the present invention. The diffusion depth d F, i.e. the maximum distance that atoms or ions of the electrode material 2 penetrate into the carrier material 1, is 36.8 μm. The diffusion depth d has been determined based on the different contrasts or different grays at the joint surface 8 with reference to the images recorded with an electron microscope. F Energy dispersive x-ray spectroscopy (EDX) from EDAX in combination with a solid-state backscattered electron imaging system (SSBSED) and an ETD (secondary electron detector) was used here.

[0064] Figure 7 Analytical diagram showing the material concentration distribution of the electrode material 2 and the carrier material 1 at the joint surface 8. Figure 7 The concentrations of the individual elements measured by energy dispersive x-ray (EDX) in FIG. 8 show that both rhodium (labeled "RhL" by the intensity of the rhodium L line) and platinum (labeled "PtL" by the intensity of the platinum L line) have penetrated into the nickel material (labeled "NiK" by the intensity of the nickel K line) of the support material 1 from the original joint surface 8 in decreasing concentrations. A diffusion zone is formed from the joint surface 8, in which nickel atoms or ions and rhodium and platinum ions or atoms diffuse from the original joint surface 8 toward the support material 1 along the diffusion depth d F Present in decreasing concentrations. Figures 5 to 7 The surprising effect achieved by the production method according to the invention is that a diffusion zone is formed starting from the joint surface 8 , in which atoms or ions of the electrode material 2 penetrate into the carrier material 1 , so that a two-dimensional bond is formed between the carrier material 1 and the electrode material 2 .

[0065] Figures 8 to 10 Further electron microscope images showing the bond between carrier material 1 and electrode material 2 in an alternative embodiment. Carrier material 1 consists of the nickel alloy VDM Nickel 201, also known as EN 2.4068, and electrode material 2 consists of the iridium-rhodium alloy IrRh 90 / 10 from the company Heraeus. Figures 8 to 10 It is evident from the figure that a diffusion zone is formed at the joint surface 8, in which ions or atoms of the electrode material 2 have diffused into the carrier material 1. The measured diffusion depth d F 22.5μm( Fig. 9 ). Figure 8 The image of the joint surface 8 is displayed at a resolution of 1024 x 943 @ 96 dpi, a bit depth of 24 and a magnification of 250:1. Fig. 9 Display resolution of 1024 x 943 @ 96 dpi, bit depth 24 and magnification of 1400:1

[0066] Fig.10Schematic diagram showing the concentration distribution of the individual atoms or ions of the individual materials of the carrier material 1 and the electrode material 2. Starting from the junction surface 8 in the direction of the carrier material 1, the concentration of rhodium and iridium decreases, while the concentration of nickel increases. Starting from the junction surface 8, a region is thus formed in the diffusion zone in which rhodium (marked as "RhL" by the intensity of the rhodium L line) and iridium (marked as "IrL" by the intensity of the iridium L line) and nickel (marked as "NiK" by the intensity of the nickel K line) atoms or ions are present, and a two-dimensional combination of these two materials is formed in the diffusion zone.

[0067] Fig.11 An alternative embodiment of an electrode produced by an optional production method with the aid of solder 13 is shown. At the joint surface 8, between the carrier material 1 and the electrode material 2, solder 13 is arranged, which has already been applied to the joint surface 8 during the production method. By applying the solder, a two-dimensional bond between the carrier material 1 and the electrode material 2 via the solder 13 is produced. Fig.11 It is clear from the figure that the electrode produced by means of solder also has a reliable two-dimensional bond between the carrier material 1 and the electrode material 2. In the production of the two-dimensional bond between the electrode material 2 and the carrier material 1, the solder 13 can be applied before or after the electrode material 2 is positioned on the carrier material 1, or the solder 13 can be introduced or placed in the joint surface 8 or at the edge or next to the joint surface 8 during the joining process. Fig.11 In the electrode produced by solder shown in FIG. 1 , the electrode material 2 consists of PtRh 90 / 10 and the carrier material 1 consists of VDM Nickel 201 or EN 2.4068. The solder 13 consists of silver solder, in this embodiment Ag 99.99 silver. The electrode material 2 is heated at 65 mN / mm 2 The surface pressure is placed against the carrier material 1 and the solder 13 is applied to the joint surface. The arrangement is positioned in ambient atmosphere and evacuated to 8 x 10 -5 mbar vacuum ( Fig.11b When the temperature reaches 650°C, an argon atmosphere of 10 mbar is applied ( Fig.11b p line in the figure).

[0068] Fig.11a The temperature profile of the heating process shown in FIG. 1 is configured so that the positioned arrangement is heated from room temperature to 650° C. within 50 minutes and further heated at 6° C. / min to a temperature of 1010° C. for a holding time of 5 minutes, followed by cooling to room temperature. This allows the solder 13 to be heated from a temperature above its melting temperature T S,焊料 (about 960°C) to below the melting temperature T of the solder 13 S,焊料 The bonding time t F 14 minutes. Therefore, the melting temperature T of the solder 13 is exceeded. S,焊料, and the melting temperature of the support material 1 and the electrode material 2 is not reached. After the cooling process, a microsection photograph is then made and examined with an electron microscope of the JEOL-JSM-IT200-LA type with an EDX unit under high vacuum. The image obtained by electron microscopy is depicted at a magnification of 80:1. Fig.11 .

[0069] The slurry was prepared by grinding with Struers films (grain sizes 220, 500, 800, 1000, 1200) for about 1 minute each, fine grinding with DiaPro Largo 9μ on MD Largo for about 5 minutes, polishing with DiaPro Floc 3μ on MD Floc for about 3 minutes and final polishing with Diapro Nap 1μ on MD Nap for about 3 minutes. Fig.11 Microscopic section shown in .

[0070] Fig.12 The temperature profile of the production method of the invention for two-dimensional bonding between a support material 1 and an electrode material 2 is shown. In this embodiment, the electrode material 2 consists of a palladium-rhodium alloy Pt / Rh 90 / 10 and the support material 1 consists of a nickel material VDM Nickel 201 or EN 2.4068. The electrode material 2 is placed against the support material 1 at the joint surface 8 and then subjected to a pressure of 310 mN / mm 2 The two materials, which are pressed against each other, are then positioned in a chamber for applying reduced pressure or vacuum, model MOV 643 from PVA, and the pressure can be applied by Fig.13 1x 10 of the v-line identification -5 mbar vacuum. After the vacuum was applied, the temperature in the chamber was then increased starting from room temperature to a temperature holding level of 930°C within 40 minutes and, after 30 minutes, further increased to 1120°C over a period of 30 minutes. The temperature was applied to the material by thermal radiation using a molybdenum heating element. After the electrode had cooled, it was then taken out and subjected to electron microscopy with a FEIQuanta 3D200 scanning electron microscope. Prior to the examination by electron microscopy, the electrode was processed to produce microsections, which were then examined with an electron microscope. For this purpose, the electrode was embedded by means of a hot embedding method, segmented perpendicular to the joining surface by means of a wet segmentation method, polished with the aid of a diamond suspension and analyzed by the EDX method under high vacuum. The results of this examination are shown in Figures 5 to 7 In it, platinum and rhodium atoms or ions were found to diffuse to a depth of 36.8 μm.

[0071] Figures 8 to 10 The electrodes shown in Figures 5 to 7 The electrodes shown in FIG. Fig.12 The described production method is produced in one operation. The arrangement is positioned under ambient atmosphere. After the chamber is evacuated to 5 x 10 -5 mbar vacuum ( Fig.13 After the v line in the figure, heating was performed to a holding temperature of 930°C. After a holding time of 30 minutes, heating was continued at 6.3°C / min until a bonding temperature of 1120°C was reached, and after a holding time of 4 hours, the bonding temperature was reduced to 1000°C in a vacuum (1 x 10 -5 mbar) to 830°C and heated to 500 mbar ( Fig.13 The holding time of 4 hours at 1120°C corresponds to a bonding time t of 4 hours. F ; The joining temperature of 1120°C corresponds to T of VDM Nickel 201 or EN 2.4068 S 77% and PtRh 90 / 10 from Heraeus S 60% and IrRh 90 / 10 from Heraeus S The electrode was also embedded by hot embedding, segmented perpendicular to the joint surface by wet segmentation, polished with the aid of a diamond suspension and analyzed by the EDX method under high vacuum. The images produced by electron microscopy show Figures 8 to 10 wherein a diffusion depth d of 22.5 μm of iridium and rhodium atoms or ions into the nickel material of the carrier material 1 is achieved F .

[0072] Fig.14 and Fig.15 Depicts an electrode made by the method of the present invention ( Fig.14 ) and an electrode made by a laser welding method known in the prior art ( Fig.15 , IrRh 90 / 10 electrode sheets on a nickel support from Bosch, produced by laser beam welding). Fig.14 It is obvious that the electrode produced by the production method of the present invention forms a full-surface bond between the electrode material 2 and the carrier material 1 without cracks and shrinkage holes, and a strong and permanent bond is achieved between the two materials. Fig.15 It is obvious from the figure that the electrodes known in the prior art do not form a full-surface bond between the carrier material 1 and the electrode material 2, but rather have a clear material boundary at the joint surface 8. Fig.15As shown in the lower left frame in FIG. 1 in an enlarged form, the electrodes known from the prior art also have bonding only in the region of the linear weld seam S, but no bonding between the carrier material 1 and the electrode material 2 in the region of the joint surface 8 beyond its edge region. Therefore, within the specimen, no bonding between the carrier material 1 and the electrode material 2 is achieved outside the weld zone extending approximately 50 μm to 100 μm into the specimen. Fig.15 It is also evident that the electrodes known from the prior art have defects caused by the mechanical clamping of the materials to each other (upper right box, Fig.15 ), where, according to research, there is an increased susceptibility to corrosion.

[0073] exist Fig.14 and Fig.15 In a comparison of the present invention, it was found in an analysis conducted by electron microscopy and further examination of the spent electrodes that the production method of the present invention achieves a full-surface bonding of the carrier material 1 and the electrode material 2, which, compared with the prior art, enables the spark plug or ignition device made of the electrode to have a higher strength and thus a longer service life. The uniform full-surface bonding between the electrode material and the carrier material by the method of the present invention also achieves a better heat transfer or a higher heat conduction than in the prior art, and thus an improved heat dissipation from the electrode in use, and in addition, the bonding area is protected from spark erosion and is therefore better protected.

[0074] Recorded with an electron microscope FEIQuanta 3D 200 scanning electron microscope with EDX from the company EDAX in combination with a solid-state backscattered electron imaging system (SSBSED) and a secondary electron detector (ETD or Everhart-Thornley detector) Figures 5 to 11 as well as Fig.14 and Fig.15 The image in .

[0075] like Fig.17 and 18 As shown in , it is optionally also possible for a plurality of electrode materials 2 or electrode sheets 7 to be arranged on a common carrier material 1 and to be bonded thereto simultaneously by the method according to the invention.

[0076] The electrodes produced by the method according to the invention were then incorporated into spark plugs and tested in a test device and under real conditions. After an operating time of several hours, no significant adverse effects could be seen compared to spark plugs from the prior art. The device in which the spark plug was installed was operated with combustible gas at high average pressure and relatively high temperature, without any bonding damage in the case of the spark plug according to the invention.

[0077] The ignition device and the spark plug produced according to the method of the invention have a service life of >4300 h in the inspection. Spark plugs produced according to the prior art by welding and installed in the same test device and thus exposed to the same process conditions throughout the process achieve a service life of <2000 h before failure due to wear or before exceeding the electrical and thermal load limits. However, the spark plugs of the prior art have become unusable after 1200 h to 1800 h.

[0078] The bond between the electrode material 2 and the carrier material 1 produced by the method according to the invention was found to be sufficiently strong during testing that it was not damaged by crack formation, hot gas corrosion, spark erosion or other effects that reduce the service life, which would otherwise cause the electrode sheet 7 or the electrode material 2 to fall off and cause the ignition device or spark plug to fail. In addition, it was found that the optimized heat conduction of the two-dimensional bond reduces the temperature of the electrode sheet 7 or the electrode material 2 and thus slows down the burning of the electrode material 2 compared to the ignition device or spark plug according to the prior art, which leads to a longer service life.

[0079] These advantageous effects are produced in the interplay of a strong and high-strength bond on the one hand and a (full-area) two-dimensional bond between electrode material 2 and carrier material 1 achieved by the method according to the invention on the other hand.

[0080] Fig.16 and Fig.17 Two spark plugs are shown in two different exemplary embodiments. Fig.16 The spark plug shown in has a first electrode 3, which is formed as a center electrode. The spark plug also has a second electrode 4, which is formed as a ground electrode. An ignition gap 6 is formed between the first electrode 3 and the second electrode 4, at which a spark can be formed between the first electrode 3 and the second electrode 4. The first electrode 3 and the second electrode 4 each have a carrier 5, which can consist of a nickel or iron material or an Inconel alloy or a refractory metal. An electrode sheet 7 is arranged on the carrier 5 in each case in the direction of the ignition gap 6, and an ignition spark is then generated between them. The bond between the carrier 5 and the electrode sheet 7 is produced in each case by the above-described method of the invention. The carrier 5 is designed as a carrier material 1, and the electrode sheet 7 is designed as an electrode material 2. The carrier material 5 is Fig.16 In the embodiment shown in FIG. 1 , the electrode sheet 7 is composed of a nickel material, and the electrode sheet 7 is formed of a noble metal, an iridium-rhodium alloy. The electrode sheet 7 of the electrodes 3, 4 is bonded to the carrier material 5 over the entire surface, in each case via a Figures 5 to 10 The diffusion bonding described above can also be achieved by Fig.11 The solder described may be produced with the aid of an intermediate material.

[0081] Fig.17Another alternative embodiment of the spark plug according to the invention is shown in an isometric view. The spark plug has two electrodes 3, 4, wherein the first electrode 3 is formed as a central electrode and the second electrode 4 is formed as a ground electrode. An ignition electrode 15 extends radially outward from the first electrode 3. The second electrode 4 has two electrode sheets 7 arranged opposite the ignition electrode 15 in each case. An ignition gap 6 is formed between the ignition electrode 15 and the four electrode sheets 7 arranged on the second electrode 4 in each case. The electrode sheets 7 are arranged on a carrier 5 of the ground electrode or second electrode 4 and are bonded thereto by the production method according to the invention. The carrier 5 takes the form of a carrier material 1 and the electrode sheets 7 take the form of an electrode material 2. The full-surface bond between the electrode sheets 7 and the carrier 5 is produced by the method according to the invention.

[0082] As Fig.16 and Fig.17 In the spark plug shown in the embodiment, the carrier 5 can be made of titanium, nickel or iron alloy, in particular nickel or chromium-nickel alloy, stainless steel, such as FeCrNi alloy, or Inconel alloy, such as NiCrFe, or refractory metal, such as tungsten. The electrode sheet 7 is preferably formed of a noble metal, in particular platinum, iridium, rhodium, ruthenium or an alloy thereof.

[0083] Due to the two-dimensional, preferably full-surface and stronger bond between electrode material 2 and carrier material 1 or between carrier 5 and electrode sheet 7, the spark plug of the present invention has a longer service life than the spark plugs known in the prior art, thus enabling the spark plug of the present invention to have longer service hours and reliable operation.

[0084] As Fig.16 and Fig.17 In addition to the embodiment options of the spark plug shown in , the spark plug according to the invention may also have other shapes, wherein the spark plug according to the invention has a two-dimensional, in particular full-surface and uniform, bond between electrode material 2 and carrier material 1 .

[0085] As Fig.16 and Fig.17 As an alternative to the spark plug shown in the figure, other ignition devices can also be produced by the method of the present invention, wherein the ignition device has an electrode with a carrier material 1 and an electrode material 2 that are two-dimensionally bonded by the method of the present invention. Such an ignition device can, for example, have one or more electrode pairs. Such an ignition device can, for example, be an annular gap spark plug, an axe-shaped spark plug or a crown-shaped spark plug.

[0086] Optionally, the electrode produced by the method of the present invention may also be subjected to pretreatment for positioning. For example, the electrode material 2 may be point-attached or fixed to the carrier material 1 by spot welding or laser bonding.

[0087] For embodiments of the present invention, it is advantageous to generate heat release to the bonding surface 8, the carrier material 1 and / or the electrode material 2 by induction, radiant heat or heat conduction to raise them to the bonding temperature T F of calories.

Claims

1. A method for producing an electrode for an ignition device, in particular a spark plug, wherein a metallic electrode material (2) is placed against a metallic carrier material (1) at a joint surface (8), wherein the carrier material (1) and the electrode material (2) are pressed against each other at the joint surface (8) with a specific surface pressure and positioned in a chamber in which a reduced pressure, in particular a vacuum, and / or a specific atmosphere is generated, wherein reduced pressure and / or a specific atmosphere is applied in the chamber, The joining surface (8), in particular the carrier material (1) and the electrode material (2), is uniformly heated to a joining temperature (T F ), The junction temperature (T F ) Holding time (t F ), so as to form a bond between the carrier material (1) and the electrode material (2) at the bonding surface (8), and the carrier material (1) and the electrode material (2) form a two-dimensional, in particular full-surface, uniform bond with each other starting from the bonding surface (8), Features The junction temperature (T F ) is lower than the melting temperature (T S ).

2. The method according to claim 1, characterized in that The heat is released to the joining surfaces (8), in particular the carrier material (1) and the electrode material (2), by means of induction, radiant heat or heat conduction to raise them to the joining temperature (T F ) calories.

3. The method according to claim 1 or 2, characterized in that The bonding temperature (T F ) Holding time (t F ) to form a metallic bond in the form of a metallic bond without forming an intermetallic phase between the support material (1) and the electrode material (2), wherein in particular, the diffusion of atoms and / or ions of the electrode material (2) into the support material (1) and / or the diffusion of atoms and / or ions of the support material (1) into the electrode material (2) is greater than or equal to 0.05 μm, in particular 1 μm to 100 μm, more preferably 20 μm to 40 μm.

4. A method according to any one of the preceding claims, characterised in that The support material (1) and the electrode material (2) are subjected to a pressure of 10 mN / mm 2 Up to 2500mN / mm 2 , especially 100mN / mm 2 Up to 600mN / mm 2 The minimum surface pressure presses against each other.

5. A method according to any one of the preceding claims, characterised in that The process is carried out under vacuum, under reduced pressure and / or under a low-oxygen, especially oxygen-free atmosphere and / or under an inert and / or reducing atmosphere, wherein the vacuum, reduced pressure and / or low-oxygen, especially oxygen-free atmosphere and / or the inert and / or reducing atmosphere are changed during the process.

6. A method according to any one of the preceding claims, characterised in that The junction temperature (T F ) is the melting temperature (T S ), especially 50% to 98%, more preferably 75% to 95%.

7. A method according to any one of the preceding claims, characterised in that Above the melting temperature (T S ) 30% threshold temperature (T 阈值 ) after the bonding time (t F ) is from 1 minute to 24 hours, especially from 1 hour to 4 hours, more preferably from 1 hour to 2 hours.

8. A method according to any one of the preceding claims, characterised in that The joint surface (8) has a thickness of 1 mm. 2 Up to 50mm 2 , especially 2mm 2 Up to 30mm 2 , more preferably 2mm 2 Up to 15mm 2 size.

9. A method according to any one of the preceding claims, characterised in that The electrode material (2) has a thickness of 0.05 mm to 2 mm, in particular 0.05 mm to 0.5 mm, more preferably 0.05 mm to 0.25 mm.

10. A method according to any one of the preceding claims, characterised in that The support material (1) consists of a material selected from the element groups 4 to 11 or the group of titanium, vanadium, chromium, manganese, iron, cobalt, nickel or copper, in particular of nickel, iron, chromium, molybdenum, tungsten or alloys thereof, and the electrode material (2) consists of a material selected from the element groups 4 to 11 or the group of titanium, vanadium, chromium, manganese, iron, cobalt, nickel or copper, in particular of platinum, iridium, rhodium, ruthenium, rhenium or alloys thereof.

11. A method according to any one of the preceding claims, characterised in that Before or after positioning the electrode material (2) on the carrier material (1), a solder (13) is applied or installed or introduced on the joining surface (8) and / or next to the joining surface (8), wherein the joining temperature (T F ) is above the melting temperature of the solder and in each case below the melting temperature (T S ), wherein the melting temperature (T S ) after the bonding time (t F ) is particularly from 10 seconds to 2 hours, preferably from 1 minute to 60 minutes.

12. The method according to claim 11, characterized in that The solder base material of the solder (13) is selected from materials of element groups 9 to 11 or cobalt, nickel or copper groups or alloys thereof, wherein the solder base material of the solder (13) in particular contains alloying additives from element groups 4 to 15, wherein the solder (13) is in particular composed of silver, gold or nickel as solder base material and preferably contains additives of chromium, silicon, boron, iron, molybdenum, phosphorus, palladium and / or copper and / or combinations thereof, wherein the solder is preferably Ag99.99 or NiCrSiBFe or NiCrSi.

13. A method according to any one of the preceding claims, characterised in that The carrier material (1) has a recess (11), wherein the electrode material (2) is at least partially sunken into the recess (11) when placed against the carrier material (1).

14. A method according to any one of the preceding claims, characterised in that An intermediate material (12) is arranged on the carrier material (1) or the electrode material (2) between the carrier material (1) and the electrode material (2), wherein the joint surface (8) is formed in each case between the carrier material (1) and the intermediate material (12) and between the electrode material (2) and the intermediate material (12), wherein the joint temperature (T F ) is lower than the melting temperature (T S ), wherein in each case the carrier material (1) and the intermediate material (12) form a two-dimensional bond with one another, and the electrode material (2) and the intermediate material (12) form a two-dimensional bond with one another.

15. The method according to claim 14, characterized in that The intermediate material (12) is in the form of a diffusion accelerating material, in particular silver or copper, wherein the intermediate material (12) accelerates the diffusion of atoms and / or ions of the electrode material (2) into the carrier material (1) via the intermediate material (12), and / or the diffusion of atoms and / or ions of the carrier material (1) into the electrode material (2) via the intermediate material (12).

16. A method according to any one of the preceding claims, characterised in that The carrier material (1) and / or the electrode material (2), in particular and / or the intermediate material (12), have an average roughness Ra of 0.01 μm to 6.3 μm, in particular 0.02 μm to 0.5 μm, at the joining surface (8).

17. A method according to any one of the preceding claims, characterised in that A plurality of carrier materials (1) and electrode materials (2) are each stacked in pairs to form a stack, wherein the carrier materials (1) and electrode materials (2) to be combined in pairs are in each case separated from each other by separator materials (19) and / or separator layers.

18. A method for producing a spark plug, in particular a spark plug for an internal combustion engine or a gas engine, wherein a first electrode (3), in particular a center electrode, and a second electrode (4), in particular a ground electrode, are formed, wherein an ignition gap (6) is formed between the first electrode (3) and the second electrode (4), in particular between the center electrode and the ground electrode, wherein a carrier (5) formed of a carrier material (1) is formed at the first electrode (3), in particular the central electrode, and / or the second electrode (4), in particular the ground electrode, wherein an electrode sheet (7) consisting of an electrode material (2) and facing in the direction of the ignition gap (6) is arranged on the carrier (5), Features The bond between the carrier (5) and the electrode sheet (7) is produced by a method according to any one of claims 1 to 17.

19. A spark plug, in particular for an internal combustion engine or a gas engine, produced in particular by the method according to claim 18, comprising a first electrode (3), in particular a center electrode, and a second electrode (4), in particular a ground electrode, wherein an ignition gap (6) is formed between the first electrode (3), in particular the center electrode, and the second electrode (4), in particular the ground electrode, wherein the first electrode (3), in particular the central electrode, and / or the second electrode (4), in particular the ground electrode, has a carrier (5), in particular a nickel carrier, on which an electrode sheet (7) is arranged in the direction of the ignition gap (6), Features The bond between the carrier (5) and the electrode sheet (7) is produced by a method according to claims 1 to 17, wherein the carrier (5) is in the form of the carrier material (1) and the electrode sheet (7) is in the form of the electrode material (2).

20. The spark plug according to claim 19, characterized in that The support (5) is formed from a titanium, nickel or iron material, in particular from a nickel or chromium-nickel alloy or steel or Inconel or a refractory metal, preferably from nickel in pure form, a nickel-based alloy, FeCrNi or FeCrNiMo stainless steel, and the electrode sheet (7) is formed from a noble metal, in particular platinum, iridium, rhodium, ruthenium, rhenium or an alloy thereof, in particular a platinum / rhodium, platinum / rhenium, platinum / iridium, iridium / rhenium or iridium / rhodium alloy, More preferably, the electrode sheet (7) comprises an alloy of PtRh 90 / 10 and the carrier (5) comprises an alloy of VDM Nickel 201 or EN 2.4068, or the electrode sheet (7) comprises an alloy of IrRh 90 / 10 and the carrier (5) comprises an alloy of VDM Nickel 201 or EN 2.4068.

21. An ignition device, in particular an ignition device for an internal combustion engine or a gas engine, comprising a first electrode (3), in particular a central electrode, and a second electrode (4), in particular a ground electrode, wherein an ignition gap (6) is formed between the first electrode (3), in particular the central electrode, and the second electrode (4), in particular the ground electrode, wherein the first electrode (3), in particular the central electrode, and / or the second electrode (4), in particular the ground electrode, has a carrier (5), in particular a nickel carrier, on which an electrode sheet (7) is arranged in the direction of the ignition gap (6), Features The carrier (5) and the electrode sheet (7) have a two-dimensional, in particular full-surface, uniform bond to one another, wherein the bond between the carrier (5) and the electrode sheet (7) is produced by a method according to claims 1 to 17, wherein in particular the carrier (5) is in the form of the carrier material (1) and the electrode sheet (7) is in the form of the electrode material (2), wherein a diffusion zone is formed in the two-dimensional bonding region between the carrier (5) and the electrode sheet (7), wherein there is a concentration of the material of the carrier (5) of 100% to 0% in the direction from the carrier (5) toward the electrode sheet (7), and a concentration of the material of the electrode sheet (7) of 0% to 100% in the direction from the carrier (5) toward the electrode sheet (7), In particular, the diffusion depth is greater than or equal to 0.05 μm, particularly 1 μm to 100 μm, and more preferably 20 μm to 40 μm.

22. The ignition device according to claim 21, characterized in that The support (5) is formed from a titanium, nickel or iron material, in particular from a nickel or chromium-nickel alloy or steel or Inconel or a refractory metal, preferably from nickel in pure form, a nickel-based alloy, FeCrNi or FeCrNiMo stainless steel, and the electrode sheet (7) is formed from a noble metal, in particular platinum, iridium, rhodium, ruthenium, rhenium or an alloy thereof, in particular a platinum / rhodium, platinum / rhenium, platinum / iridium, iridium / rhenium or iridium / rhodium alloy, More preferably, the electrode sheet (7) comprises an alloy of PtRh 90 / 10 and the carrier (5) comprises an alloy of VDM Nickel 201 or EN 2.4068, or the electrode sheet (7) comprises an alloy of IrRh 90 / 10 and the carrier (5) comprises an alloy of VDM Nickel 201 or EN 2.4068.

Citation Information

Patent Citations

  • Spark plug

    DE112016006310T5

  • spark plug

    DE112019000377T5

  • Clad electrode for spark plug, and method for manufacturing the same

    EP2738890A1

  • Spark plug and method for producing the same

    EP3139457A1

  • Spark plug and method for producing a spark plug

    EP3694684A1